Environmental influences on the recruitment dynamics of juvenile European eels, Anguilla anguilla, in a small estuary of the Tyrrhenian Sea, Sardinia, Italy. Issue 8 (7th June 2020) - Podda, Cinzia; Palmas, Francesco; Frau, Giacomo; Chessa, Giovanna; Culurgioni, Jacopo; Diciotti, Riccardo; Fois, Nicola; Sabatini, Andrea
Abstract: The European eel, Anguilla anguilla, is a catadromous and migratory species of commercial importance. Its complex life cycle results in its exposure to many risk factors, which have resulted in stock declines across all life stages since the 1970s. The temporal recruitment dynamics of juvenile eels (glass eels and elvers) were investigated in a small Mediterranean estuary (Sardinia, Italy). The composition of the population and the monthly and seasonal variations in the abundances of juvenile eels was assessed over 78 sampling events (from February 2017 to February 2018). Furthermore, the effects of abiotic variables on the abundances of glass eels and elvers were investigated using generalized additive models (GAMs). Glass eels had the greatest abundance during the winter months, whereas elvers had the greatest abundance during spring. Modelling revealed that the abundance of glass eels was mostly explained by the combined effects of water temperature (12.3–14.5 °C), tidal coefficient (40–110 cm), moon phase, season, and river mouth condition, whereas the abundance of elvers was associated with water temperature (14–21 °C), dissolved oxygen content (>7 mg/L), and season. These results suggest that the annual recruitment of juvenile eels occurs throughout the year, with clear seasonal migration dynamics. The use of multiple statistical approaches allowed us to identify the importance of several environmental variables in regulating the recruitment dynamics, providing useful information for conserving eel stocks through the restoration of the natural flow regime and the connectivity between freshwater habitats and the sea.